Upaya Pemanfaatan Limbah Pertanian di Nagari Koto Tangah, Kecamatan Tilatang Kamang, Kabupaten Agam - Swastiko Priyambodo; Firza Rahayu; Suci Maharani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
The habit of the people of Nagari Koto Tangah who burns straws a form of handling the agriculture waste causes pollution to the environment, then the used of chemical fertilizer reduced soil fertility. The community empowerment program through Thematic Student Service Learning aims to provide education and assistance for farming communities to be able to carry out proper handling of agriculture waste, especially straw. One of the measures that can be taken is processing the straw waste into compost. The activity was starting with the socialization on the benefits of using straw compost, continued with practice of making compost from straw. The activity was attended by the Barokah women farmer group and accompanied by the Tilatang Kamang Agricultural Extension Center. This activity was appreciated by farming community and had a positive impact on the farming community in the form of increasing community knowledge and skills in processing straw waste into compost. The continuity of the program running well when the level of awareness of the farming community is high and is supported and facilitated by the Tilatang Kamang Agricultural Extension Center. Keywords: agricultural extension center, compost, organic fertilizer, straw, thematic student service learning